2001
DOI: 10.3758/bf03196397
|View full text |Cite
|
Sign up to set email alerts
|

The representations of the arithmetic operations include functional relationships

Abstract: Current theories of mathematical problem solving propose that people select a mathematical operation as the solution to a problem on the basis of a structure mapping between their problem representation and the representation of the mathematical operations. The structure-mapping hypothesis requires that the problem and the mathematical representations contain analogous relations. Past research has demonstrated that the problem representation consists of functional relationships, or principles. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
4
35
0
2
Order By: Relevance
“…Recent research has also highlighted other diYculties that adults and children have with division. Dixon, Deets, and Bangert (2001) found that eighth-graders' and adults' understanding of the concept of division is signiWcantly weaker than that of the other operations, and Squire and Bryant (2003) highlighted the diYculties that younger children have with concrete representations of division.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research has also highlighted other diYculties that adults and children have with division. Dixon, Deets, and Bangert (2001) found that eighth-graders' and adults' understanding of the concept of division is signiWcantly weaker than that of the other operations, and Squire and Bryant (2003) highlighted the diYculties that younger children have with concrete representations of division.…”
Section: Discussionmentioning
confidence: 97%
“…Less time may be spent teaching, learning, and exploring this operation than is the case with the other operations. Dixon, Deets, and Bangert (2001) found that operations learned later tend to have weaker principle representations. Most children and many adults solve simple division problems (e.g., 48 ‚ 6) often by using related multiplication facts and rarely by retrieving division facts directly (Robinson, Arbuthnott, & Gibbons, 2002;Robinson et al, in press).…”
Section: Importance Of Examining Performance On Two Types Of Inversiomentioning
confidence: 97%
“…In the context of numerical problem solving, mathematical modeling entails choosing an arithmetic operation that corresponds to the situation described in the problem text. College students have extensive experience with this modeling task, and are highly fluent in selecting arithmetic operations that are structurally analogous to the quantitative relations in word problems (e.g., Bassok, Chase, & Martin, 1998;Bassok, Wu, and Olseth, 1995;Dixon, 2005;Dixon, Deets & Bangert, 2001;Martin & Bassok, 2005). When students transition to algebra and learn that algebraic models have a standard (multiplication) form, some of them may be unsure whether and, if so, how algebraic modeling involves selecting an appropriate arithmetic operation.…”
Section: Introductionmentioning
confidence: 99%